1999
DOI: 10.1046/j.1365-2346.1999.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of topical lignocaine spray applied before or after induction of anaesthesia on the pressor response to direct laryngoscopy and intubation

Abstract: In an attempt to attenuate the cardiovascular pressor response to laryngoscopy and intubation, 30 patients presenting for routine ophthalmic surgery were studied and were randomly allocated into two groups: group A (n = 15) received direct laryngeal/tracheal lignocaine spray immediately before intubation; and group B (n = 15) received orolaryngeal lignocaine spray before the induction of anaesthesia. In both groups, general anaesthesia was induced with thiopentone 3-5 mg kg-1, followed by atracurium 0.6 mg kg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…The efficacy of tracheal lidocaine for attenuation of the cardiovascular responses to tracheal intubation has not been fully established and some authors have questioned its efficacy. [8][9][10] It is unknown whether the magnitude of the cardiovascular responses to tracheal lidocaine alone is less than that of endotracheal intubation without topical anesthesia. If the magnitude of the cardiovascular responses to tracheal lidocaine alone is as great as that produced by endotracheal intubation, it would have limited usefulness as an attenuating drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of tracheal lidocaine for attenuation of the cardiovascular responses to tracheal intubation has not been fully established and some authors have questioned its efficacy. [8][9][10] It is unknown whether the magnitude of the cardiovascular responses to tracheal lidocaine alone is less than that of endotracheal intubation without topical anesthesia. If the magnitude of the cardiovascular responses to tracheal lidocaine alone is as great as that produced by endotracheal intubation, it would have limited usefulness as an attenuating drug.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In the study of Denlinger et al, 11 endotracheal intubation was performed more than two minutes after a tracheal spray with local anesthetics while endotracheal intubation was performed less than one minute after topical anesthesia in the studies that indicated the ineffectiveness of tracheal lidocaine. [8][9][10] Our study suggests that differing intervals between tracheal lidocaine and endotracheal intubation probably caused the inconsistent conclusions reported in other investigations. Our results show that endotracheal intubation performed two minutes after tracheal lidocaine attenuates the cardiovascular responses to endotracheal intubation.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
“…Although there may be systemic absorption of topical lidocaine administered as an oropharyngeal spray, Mostafa et al 22 found that the plasma lidocaine concentrations after topical lidocaine 3 mgÁkg -1 (0.8 ± 0.41 lgÁmL -1 ) were well below the toxic range (5-9 lgÁmL -1 ). We chose to use an even lower dose of topical lidocaine (40 mg) because this dose has been found to be effective in improving LMA insertion conditions.…”
mentioning
confidence: 99%
“…Several studies have examined the efficacy of tracheal lidocaine in attenuating the hemodynamic responses to endotracheal intubation [9,19,20], with inconsistent results, depending on the timing of lidocaine administration. Tracheal administration of lidocaine 1 min before tracheal intubation was ineffective for attenuation of the cardiovascular response to intubation [19,20].…”
Section: Discussionmentioning
confidence: 99%